Pra-Pelaksana Verifikasi Data pada Program Bantuan Kursi Roda Disabilitas Terindeks DTKS di Kecamatan Medan Helvetia - Fanny Pratiwi; Fajar Utama Ritonga (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2024)
A physical, intellectual or mental disability that prevents a person from carrying out activities or interacting with their environment independently is known as a disability. The problems that people with disabilities often face in Indonesia, especially people with low economic conditions, include lack of access to information about the importance of rehabilitation and lack of public facilities that make it easier for people with disabilities to carry out daily activities. Disabled people need wheelchair assistive devices to improve their accessibility and mobility. So there is a goal of this community service as an important effort to help recipients of assistance so they can be verified and receive the assistance. This activity is accompanied by Social Workers from the Medan City Social Service for the Wheelchair Assistance Program which requires verification and validity of data so that the Wheelchair Assistance Program for Disabled People is indexed. in Medan City's Integrated Social Data (DTKS) right on target. This article uses qualitative methods with literature studies and field activities. Pre-implementation of this program involves the stages of identification, application submission, and data verification. The results obtained were that of the 3 disabilities recorded, there were only 2 disabilities registered by DTKS in Medan Helvetia District which were verified and valid from data on requests for wheelchair assistance. This Community Service output also produces information regarding disability assistance which must be indexed in the Integrated Social Data (DTKS) in Medan City.